The Impact of Work-Life Balance and Compensation on Police Job Satisfaction at the West Sumatra Regional Police - Vita Mayastinasari; Ekawaty Kristianingsih (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Police duties, characterised by a heavy workload, long working hours and significant responsibilities, often make it difficult for police officers to balance their work and personal lives. Such circumstances may shape the degree of job satisfaction experienced by police officers. In addition, the remuneration provided by the organisation also represents an important element capable of affecting job satisfaction. Consequently, it is necessary for police institutions to pay attention to work–life balance and an equitable compensation system in order to enhance officers’ job satisfaction. This study aims to examine the influence of work–life balance and compensation on the job satisfaction of personnel within the West Sumatra Regional Police. This research adopts a quantitative approach using a survey method involving 389 officers from the West Sumatra Regional Police who were selected through random sampling. Data were obtained through a questionnaire measured with a five-point Likert scale and analysed using multiple linear regression with the assistance of SPSS. The findings reveal that work–life balance exerts a positive and significant effect on the job satisfaction of police officers. Likewise, compensation demonstrates a positive and significant influence on officers’ job satisfaction. These findings indicate that an appropriate balance between occupational duties and personal life, together with fair compensation, can improve the level of job satisfaction among police officers. This study suggests that police institutions should establish policies that support work-life balance and equitable compensation systems in order to enhance job satisfaction, officers’ well-being, and overall organisational performance.